Reaction cycles and poisoning in catalysis by gold clusters: A thermodynamics approach. Issue 1 (2nd July 2013) - Beret, Elizabeth C.; van, Merel M.; Ghiringhelli, Luca M.
<x xml:space="preserve">Abstract</x> In heterogeneous catalysis, a catalytic process takes place at finite temperature and at finite pressure of the atmosphere of the reactant gases. By applying ab initio atomistic thermodynamics to the model case of free Au2 and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3xdzb1m2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Au2−</alternatives> clusters in an atmosphere of O2 and CO, we derive all the thermodynamically possible reaction paths for the oxidation of CO to CO2. This analysis lets us explain how gold clusters enable oxidation reactions without breaking the spin‐conservation rule. Furthermore, we identify special cluster + ligands compositions such as reaction intermediates and poisoned species. In particular, a thermodynamically driven poisoning is identified for the catalytic system containing free Au2, and the experimental (p, T) conditions that avoid its formation are suggested. This implies that for some systems a catalytic cycle can be established, on thermodynamics grounds, only in a defined range of temperatures and pressures. In addition, our predictions for <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3xdzb1kh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Au2−</alternatives> provide the so far most complete interpretation of the available experimental data (Socaciu et al, J. Am. Chem. Soc. 2003). © 2013 Wiley Periodicals, Inc.